Evaluating the State of Affairs of the "Biological" and "Applied" System in the Preparatory School Study from the Students' Perspective - Zainab K. Abdul-Hassan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The current research aims to: i) evaluate the practicality of the scientific system in the preparatory schools, based on two models: biological and applied branches; ii) to identify the general judgment on this system and iii) to reveal aspects of weakness and strength of each branch. The original research sample consisted of (400) male and female students of governmental secondary school (preparatory cycle) (Morning study) for boys and girls under the General Directorate of Education in Basra Governorate for the academic year (2019-2020). An exploratory questionnaire was used as a research tool where a set of questions about (the "biological" and "applied" system were presented to the students and whether they are with or against this educational system stating the reasons for their choice. After collecting and sorting the information and data, a questionnaire was prepared consisting, in its initial form, of (35) paragraphs, and in accordance with the Likert scale of three alternatives consisting of (yes, to some extent, no). It was presented to a group of arbitrators to determine whether the paragraphs are valid or not and to amend or correct some of them or add other paragraphs. The experts agreed on all the paragraphs while reformulating some of the paragraphs and thus the validity of the tool was confirmed. Then, the statistical validity was found (discriminatory) and paragraph No. (31) was ruled out and thus the questionnaire consisted of (34) items only. The reliability was found by the two half-segmentation methods and the Alpha Cronbach method. The reliability coefficient of the student sample by the half-segmentation method reached (0.58). After applying the Gutman equation, this became (0.70). The reliability coefficient of the student sample by the Alpha Cronbach method was (0.67). The scale was applied in its final form to a sample of (400) male and female students. According to the variables of sex and specialization (biological & applied), the following statistical methods were used to achieve the research objectives: T-test for one sample to find out the level of satisfaction or rejection of the research sample as well as T-test for two samples of equal number in comparison between the two groups (27%) high and (27%) low for the purpose of distinguishing the paragraphs. Also calculated is the percentage weight and this is to identify strengths and weaknesses in each paragraph of the scale from the students' point of view. In light of the research objectives, the results showed little satisfaction among students of the preparatory stage (the scientific branch) about the diverse system of their branch of study (biological and applied). It appeared that paragraph (25) in the scale (i.e high rates in the biological branch with a lack of non-medical specializations that do not provide an opportunity for admission to universities) ranked first with a weighted mean (2.775) and a weight percentage of (5.,92%). In light of these results, we presented a number of recommendations, the most important of which are: canceling the new system and returning to the (scientific and literary) system. We also put forward some proposals, the most important of which is: an analytical study of the results of the ministerial (governmental or central) examinations for the biological and applied branches.